A comprehensive finite-element human ear model to estimate noise-induced hearing loss associated with occupational noise exposure. (November 2022) - Yu, You-Cheng; Wang, Tang-Chuan; Shih, Tzu-Ching
Highlights: A comprehensive finite-element human ear model can be used to quantitatively analyze the impact of noise-induced hearing loss. Three-dimensional distribution of auditory risk units of the basilar membrane from frequency 0.2 to 10.0 kHz was demonstrated. There is consistency between numerical simulation results and clinical data associated with occupational noise exposure. Abstract: Background and objective: Noise is a common occupational and environmental hazard; however, little is known about the use of computational tools to quantitively analyze data on basilar membrane (BM) damage in noise-induced hearing loss (NIHL). Here, we established a comprehensive three-dimensional finite-element human ear model to quantify the impact of noise exposure on BM and perilymph fluid. Methods: We used auditory risk units (ARUs) to evaluate the BM damage for subjects (3 men and 5 women; mean age, 32.75 ± 8.86 years; age range, 24–44 years). A 90-dB sound pressure level (SPL) was normally applied at the external auditory canal (EAC) entrance to simulate sound transmission from the EAC to the cochlea at frequencies of 0.2–10.0 kHz. Results: The pressure distribution of perilymph fluid is totally different on frequency responses under low and high sound-evoked (0.013–10.0 kHz). The highest ARUs were 18.479% at the distance of 1 mm from the base, and the second-highest to fourth-highest ARUs occurred at distances of 5–7 mm from the base, where their ARUs were 9.749%, 9.176%, and 11.231%. The total of the ARUs reached 81.956% at external frequencies' sounds of 3.2–5.0 kHz. Among these, the 3.8-kHz and 3.6-kHz frequencies yielded the highest and second-highest ARUs of 20.325% and 19.873%, respectively. Conclusions: This study would inform our understanding of NIHL associated with occupational noise exposure. We present a FE modelling and describe how it might provide a unique way to unravel mechanisms that drive NIHL due to loud noises.